A plastic processing-heat treatment process of a nickel-titanium alloy wire for aerospace unlocker driving

By preparing nickel-titanium alloy wires through specific elemental composition and plastic processing-heat treatment process, the functional fatigue problem of nickel-titanium alloy wires in aerospace unlocking devices was solved, achieving a combination of excellent shape memory effect and high fatigue resistance, thus improving the performance and lifespan of the device.

CN120330536BActive Publication Date: 2025-11-18BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510539467.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-11-18
Estimated Expiration
2045-04-27

AI Technical Summary

Technical Problem

Existing nickel-titanium alloy wires suffer from functional fatigue failure in aerospace unlocking devices, making it difficult to balance excellent shape memory effect and high fatigue resistance, thus affecting the performance and lifespan of the device.

Method used

Nickel-titanium alloy wire with a specific elemental composition is prepared through a plastic processing-heat treatment process, including forging, hot rolling, hot drawing, intermediate cold drawing, and finished product annealing, resulting in nickel-titanium alloy wire with excellent shape memory effect and high fatigue resistance.

Benefits of technology

It improves the shape memory effect and fatigue resistance of nickel-titanium alloy wire, reduces plastic accumulation, and extends the service life of aerospace unlocking devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120330536B_ABST
    Figure CN120330536B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of spacecraft equipment element manufacturing, and particularly relates to a nickel-titanium alloy wire plastic processing-heat treatment process for driving a spacecraft unlocking device. The element components of the nickel-titanium alloy wire include 49.9-50.1% of Ni and the balance of Ti and inevitable other impurity elements in terms of weight percentage. The impurity content is less than 0.01% of C, less than 0.05% of O, less than 0.001% of N and less than 0.0002% of H in terms of weight percentage. The nickel-titanium alloy wire has excellent shape memory effect, high fatigue resistance and low plastic accumulation, and can improve the performance and service life of the spacecraft unlocking device when used in the spacecraft unlocking device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of spacecraft equipment component manufacturing technology, and in particular relates to a process for plastic forming and heat treatment of nickel-titanium alloy wire for aerospace unlocking device drive. Background Technology

[0002] Nickel-titanium alloys exhibit shape memory and superelasticity effects. The shape memory effect (SME) refers to the alloy's ability to automatically return to its original shape after undergoing plastic deformation under external force and being heated above a specific temperature (transformation temperature). When nickel-titanium alloys are subjected to changes in temperature and mechanical pressure, two different crystal phases exist: austenite and martensite. When the alloy cools from the austenite phase to the martensite phase and undergoes plastic deformation, and is then reheated above the austenite transformation temperature, the martensite phase will reverse into the austenite phase, and the alloy's shape will return to its original state. The superelasticity of nickel-titanium alloys refers to their ability, under specific conditions (typically above their austenitic transformation temperature), to withstand strains far exceeding their elastic limit and recover their original shape almost entirely without residual strain upon unloading. This effect originates from the martensitic transformation and its inverse transformation under stress. When the alloy is in the austenitic state, external forces induce a martensitic transformation, leading to significant deformation. However, once the force is removed, the martensitic phase transforms back into the austenitic phase, and the alloy's shape is restored. Nickel-titanium alloys exhibit excellent mechanical properties, biocompatibility, and corrosion resistance. In practical applications, both effects can be selectively applied through appropriate metallurgical, plastic deformation, and heat treatment processes. Furthermore, appropriate processing techniques can alter the properties of a particular effect, such as the transformation point and recovery strain rate, to adapt it to different extreme environments.

[0003] Currently, most research on the shape memory and superelastic effects of nickel-titanium alloys is conducted at room temperature. In this case, nickel-titanium alloys can be fundamentally classified into two categories based on their alloy composition, thus altering their phase transformation behavior. For example, near-equal-atomic nickel-titanium alloys (~49.8-50.5% Ni) exhibit shape memory effects, while near-equal-atomic nickel-titanium alloys (~50.5-50.8% Ni) exhibit superelastic effects. Both types of nickel-titanium alloys have been commercially available for decades. Generally, conventional nickel-titanium alloys with room-temperature superelastic and shape memory effects have nickel contents of 50.8% Ni and 50.0% Ni, respectively. The nature of these effects depends on the phase transformation behavior determined by the chemical composition and manufacturing process. Because the shape memory effect allows nickel-titanium alloy wires to output force by applying an electric current after being subjected to moderate deformation (approximately 5% strain), nickel-titanium shape memory alloys are widely used in intelligent actuation applications such as adaptive wings, high-reliability locking and releasing devices, and aerospace unlocking devices.

[0004] Although nickel-titanium alloy wires possess outstanding shape memory effects and are widely used in smart structures, functional fatigue remains the most common failure mode in shape memory alloy-driven aerospace unlocking devices during service. Research indicates that the root cause of these failures is the irreversible accumulation of plastic strain in the shape memory alloy material during repeated drive-reset cycles. This leads to relaxation, causing the material to deviate from its initial assembly position. Consequently, the drive displacement fails to reach the design value, and the shape memory alloy material cannot drive the entire device to unlock. Therefore, the lifespan of the entire aerospace unlocking device directly depends on the functional fatigue performance of the shape memory alloy material, significantly reducing the device's performance and service life.

[0005] However, for nickel-titanium alloy wires, the excellent shape memory effect and high fatigue resistance are like an irreconcilable contradiction. High nickel content alloy wires often exhibit excellent shape memory effect, but they are difficult to cope with the challenge of functional fatigue. In order to pursue better fatigue resistance, their shape memory ability is usually sacrificed, making it difficult to achieve both excellent shape memory effect and high fatigue resistance. In order to find a nickel-titanium alloy wire that has both excellent shape memory effect and high fatigue resistance, improve the performance and service life of aerospace unlocking devices, reduce design redundancy, and reduce costs, those skilled in the art have conducted long-term research in order to find the best balance point, but the results have not been ideal.

[0006] In view of the above, this application is hereby submitted. Summary of the Invention

[0007] The purpose of this invention is to address the aforementioned technical problems by providing a plastic forming and heat treatment process for nickel-titanium alloy wire used in aerospace unlocking devices. This process yields nickel-titanium alloy wires with excellent shape memory effect, high fatigue resistance, and low plasticity accumulation, thereby improving the performance and service life of aerospace unlocking devices when used in them.

[0008] In view of this, the present invention provides a plastic forming-heat treatment process for nickel-titanium alloy wire used in aerospace unlocking actuators. The elemental composition of the nickel-titanium alloy wire, by weight percentage, includes: 49.9-50.1% Ni, with the balance being Ti and other unavoidable impurity elements; wherein the impurity content, by weight percentage, is: C < 0.01%, O < 0.05%, N < 0.001%, H < 0.0002%.

[0009] Furthermore, the plastic forming-heat treatment process of the nickel-titanium alloy wire includes the following steps:

[0010] S1, forging: heating the alloy ingot and then forging it into a square ingot;

[0011] S2, Hot rolling: Square ingots are hot rolled through a multi-pass square-round-square profile until the bar diameter is ≤ Φ8mm;

[0012] S3, Hot drawing: The bar is hot drawn in multiple passes until the bar diameter is ≤ Φ3mm;

[0013] S4, intermediate cold drawing: The bar is subjected to multiple cold drawing passes, wherein the deformation per pass of intermediate cold drawing is 5% to 20%, and the cumulative deformation of intermediate cold drawing is 29% to 60%.

[0014] S5, intermediate annealing treatment: intermediate annealing treatment is carried out on the bar after intermediate cold drawing. The intermediate annealing treatment regime is: heating temperature 680~750℃, holding time 1~3min, and cooling method is air cooling or wind cooling.

[0015] S6. Repeat steps S4 to S5 until the diameter of the bar reaches Φ0.5 to 2 mm.

[0016] S7, Final Cold Drawing: The bar is cold drawn in multiple passes until the size of the cold-drawn wire meets the requirements of the finished product size. The deformation amount of a single pass in the final cold drawing is 5% to 20%.

[0017] S8, Finished product annealing treatment: After the final cold-drawn wire is subjected to finished product annealing treatment, the nickel-titanium alloy wire is obtained.

[0018] Furthermore, the diameter of the nickel-titanium alloy wire is Φ0.32~0.42mm.

[0019] Furthermore, in step S1, the diameter of the alloy ingot is Φ80~120mm; the heating temperature is 850-880℃; the holding time is 80~100min; and the side length of the cross section of the forged ingot is 60~40mm.

[0020] Furthermore, in step S2, the hot rolling parameters are: heating temperature of 850-880℃, holding time of 30-50min, and hot rolling through a multi-pass square-round-square die to a bar diameter of Φ6-8mm.

[0021] Furthermore, in step S3, the hot drawing parameters are: heating temperature of 700-850℃, holding time of 35-48min, and after multiple hot drawing passes, the diameter of the bar is Φ1-3mm.

[0022] Furthermore, in step S7, the cumulative deformation of the final cold drawing is ≥40%.

[0023] Furthermore, in step S8, the finished product annealing process is as follows: heating temperature 400-450℃, holding time 30-60min, and cooling method is air cooling.

[0024] A nickel-titanium alloy wire for driving an aerospace unlocker, wherein the nickel-titanium alloy wire is prepared by the aforementioned nickel-titanium alloy wire plastic processing-heat treatment process.

[0025] A spacecraft unlocking device, the spacecraft unlocking device comprising a nickel-titanium alloy wire prepared by the above-mentioned nickel-titanium alloy wire plastic processing-heat treatment process.

[0026] The beneficial effects of this invention are: the nickel-titanium alloy wire prepared by this invention has excellent shape memory effect, high fatigue resistance and low plasticity accumulation. When used in aerospace unlocking devices driven by shape memory alloy materials, it can improve the performance and service life of aerospace unlocking devices. Attached Figure Description

[0027] Figure 1 This is a process flow diagram of preparing nickel-titanium alloy wire in Example 1 of the present invention;

[0028] Figure 2 This is a photograph of the nickel-titanium alloy wire prepared in Example 1 of the present invention.

[0029] Figure 3 The stress-strain curve of the nickel-titanium alloy wire prepared in Example 1 of this invention;

[0030] Figure 4 The DSC curve and phase transformation temperature of the nickel-titanium alloy wire prepared in Example 1 of this invention;

[0031] Figure 5The drawing curve of the nickel-titanium alloy wire prepared in Example 1 of this invention is a result of 100 stretch-heat cycles.

[0032] Figure 6 The thermal cycle curve of a commercially available nickel-titanium alloy wire after 100 cycles;

[0033] Figure 7 This is a sampling location diagram for microstructure detection of the nickel-titanium alloy wire prepared in Example 1 of the present invention;

[0034] Figure 8 This is a microstructure diagram of the nickel-titanium alloy wire prepared in Example 1 of the present invention. Detailed Implementation

[0035] The technical solutions in this application will be clearly described below with reference to specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments in this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application are within the scope of protection of this application.

[0036] In the description of this application, it should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. For ease of description, techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values.

[0037] It should be noted that, in this application, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element. Furthermore, it should be noted that the scope of the methods and apparatuses in the embodiments of this application is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. Additionally, features described with reference to certain examples may be combined in other examples.

[0038] A plastic forming-heat treatment process for a nickel-titanium alloy wire used in aerospace unlocking devices, wherein the elemental composition of the nickel-titanium alloy wire, by weight percentage, comprises: 49.9-50.1% Ni, with the balance being Ti and other unavoidable impurity elements; wherein the impurity content, by weight percentage, is: C < 0.01%, O < 0.05%, N < 0.001%, H < 0.0002%.

[0039] Furthermore, such as Figure 1 As shown, the plastic forming-heat treatment process of the nickel-titanium alloy wire includes the following steps:

[0040] S1, forging: heating the alloy ingot and then forging it into a square ingot;

[0041] S2, Hot rolling: Square ingots are hot rolled through a multi-pass square-round-square profile until the bar diameter is ≤ Φ8mm;

[0042] S3, Hot drawing: The bar is hot drawn in multiple passes until the bar diameter is ≤ Φ3mm;

[0043] S4, intermediate cold drawing: The bar is subjected to multiple cold drawing passes, wherein the deformation per pass of intermediate cold drawing is 5% to 20%, and the cumulative deformation of intermediate cold drawing is 29% to 60%.

[0044] S5, intermediate annealing treatment: intermediate annealing treatment is carried out on the bar after intermediate cold drawing. The intermediate annealing treatment regime is: heating temperature 680~750℃, holding time 1~3min, and cooling method is air cooling or wind cooling.

[0045] S6. Repeat steps S4 to S5 until the diameter of the bar reaches Φ0.5 to 2 mm.

[0046] S7, Final Cold Drawing: The bar is cold drawn in multiple passes until the size of the cold-drawn wire meets the requirements of the finished product size. The deformation amount of a single pass in the final cold drawing is 5% to 20%.

[0047] S8, Finished product annealing treatment: After the final cold-drawn wire is subjected to finished product annealing treatment, the nickel-titanium alloy wire is obtained.

[0048] Preferably, the diameter of the nickel-titanium alloy wire is Φ0.32~0.42mm.

[0049] Furthermore, in step S1, the diameter of the alloy ingot is Φ80~120mm; the heating temperature is 850-880℃; the holding time is 80~100min; and the side length of the cross section of the forged ingot is 60~40mm.

[0050] Furthermore, in step S2, the hot rolling parameters are: heating temperature of 850-880℃, holding time of 30-50min, and hot rolling through a multi-pass square-round-square die to a bar diameter of Φ6-8mm.

[0051] Furthermore, in step S3, the hot drawing parameters are: heating temperature of 700-850℃, holding time of 35-48min, and after multiple hot drawing passes, the diameter of the bar is Φ1-3mm.

[0052] Furthermore, in step S7, the cumulative deformation of the final cold drawing is ≥40%.

[0053] Furthermore, in step S8, the finished product annealing process is as follows: heating temperature 400-450℃, holding time 30-60min, and cooling method is air cooling.

[0054] In addition, the present invention also provides a nickel-titanium alloy wire for driving aerospace unlocking devices, wherein the nickel-titanium alloy wire is prepared by the above-mentioned nickel-titanium alloy wire plastic processing-heat treatment process.

[0055] And, a space unlocking device, wherein the space unlocking device is driven by a shape memory alloy material, wherein the shape memory alloy material used in the space unlocking device is a nickel-titanium alloy wire prepared by the above-mentioned nickel-titanium alloy wire plastic processing-heat treatment process.

[0056] Example 1

[0057] A nickel-titanium alloy wire for driving a space unlocker

[0058] The elemental composition of the nickel-titanium alloy wire, by weight percentage, includes: 50.0% Ni, with the balance being Ti and other unavoidable impurity elements; wherein the impurity content, by weight percentage, is: C < 0.01%, O < 0.05%, N < 0.001%, H < 0.0002%.

[0059] The plastic forming and heat treatment process of the nickel-titanium alloy wire used for driving the aerospace unlocker is as follows:

[0060] S1, Forging: The alloy ingot is heated and then forged into a square ingot; wherein the diameter of the alloy ingot is Φ100mm; the heating temperature is 860℃, the holding time is 90min, and the side length of the cross section of the forged square ingot is 50mm.

[0061] S2, Hot rolling: The square ingot is hot rolled through a multi-pass square-round-square profile until the bar diameter is Φ8mm; the hot rolling parameters are: heating temperature is 870℃, and holding time is 40min;

[0062] S3, Hot drawing: The bar is hot drawn in multiple passes until the diameter of the bar is Φ3mm; the hot drawing parameters are: heating temperature is 800℃, and holding time is 40min.

[0063] S4, intermediate cold drawing: The bar is subjected to multiple cold drawing passes, wherein the deformation per pass of intermediate cold drawing is 10-15%, and the cumulative deformation of intermediate cold drawing is 40-60%.

[0064] S5, Intermediate Annealing Treatment: The cold-drawn bar is subjected to intermediate annealing treatment. The intermediate annealing treatment process is as follows: heating temperature 700℃, holding time 2min, and cooling method is air cooling.

[0065] S6. Repeat steps S4 to S5 until the diameter of the bar reaches Φ0.5mm;

[0066] S7, Final Cold Drawing: The bar is cold drawn in multiple passes until the wire size reaches Φ0.38mm. The deformation per pass of the final cold drawing is 10-15%; the cumulative deformation of the final cold drawing is 42%.

[0067] S8, Finished product annealing: The final cold-drawn wire undergoes a finished product annealing process. The annealing process is as follows: heating temperature 430℃, holding time 50min, and air cooling. After annealing, the nickel-titanium alloy wire is obtained, with a diameter of Φ0.38mm. (The actual product is shown in the image.) Figure 2 As shown.

[0068] Example 2

[0069] A nickel-titanium alloy wire for driving a space unlocker

[0070] The elemental composition of the nickel-titanium alloy wire, by weight percentage, includes: 49.9% Ni, with the balance being Ti and other unavoidable impurity elements; wherein the impurity content, by weight percentage, is: C < 0.01%, O < 0.05%, N < 0.001%, H < 0.0002%.

[0071] The plastic forming and heat treatment process of the nickel-titanium alloy wire used for driving the aerospace unlocker is as follows:

[0072] S1, Forging: The alloy ingot is heated and then forged into a square ingot; wherein the diameter of the alloy ingot is Φ80mm; the heating temperature is 850℃, the holding time is 80min, and the side length of the cross section of the forged square ingot is 60mm.

[0073] S2, Hot rolling: The square ingot is hot rolled through a multi-pass square-round-square profile until the bar diameter is Φ7mm; the hot rolling parameters are: heating temperature is 850℃, and holding time is 30min;

[0074] S3, Hot drawing: The bar is hot drawn in multiple passes until the diameter of the bar is Φ1mm; the hot drawing parameters are: heating temperature is 700℃, and holding time is 35min.

[0075] S4, intermediate cold drawing: The bar is subjected to multiple cold drawing passes, wherein the deformation amount of a single pass of intermediate cold drawing is 5% to 10%, and the cumulative deformation amount of intermediate cold drawing is 29% to 40%.

[0076] S5, Intermediate Annealing Treatment: The cold-drawn bar is subjected to intermediate annealing treatment. The intermediate annealing treatment process is as follows: heating temperature 680℃, holding time 1min, and cooling method is air cooling.

[0077] S6. Repeat steps S4 to S5 until the diameter of the bar reaches Φ0.60mm;

[0078] S7, Final Cold Drawing: The bar is cold drawn in multiple passes until the wire size reaches the finished product size requirement of Φ0.42mm. The deformation of a single pass in the final cold drawing is 5% to 10%; the cumulative deformation of the final cold drawing is 51%.

[0079] S8, Finished product annealing treatment: The finished product annealing treatment is carried out on the final cold-drawn wire. The finished product annealing treatment process is as follows: heating temperature 400℃, holding time: 30min, cooling method is air cooling. The finished product annealing treatment yields the nickel-titanium alloy wire with a diameter of Φ0.42mm.

[0080] Example 3

[0081] A nickel-titanium alloy wire for driving a space unlocker

[0082] The elemental composition of the nickel-titanium alloy wire, by weight percentage, includes: 50.1% Ni, with the balance being Ti and other unavoidable impurity elements; wherein the impurity content, by weight percentage, is: C < 0.01%, O < 0.05%, N < 0.001%, H < 0.0002%.

[0083] The plastic forming and heat treatment process of the nickel-titanium alloy wire used for driving the aerospace unlocker is as follows:

[0084] S1, Forging: The alloy ingot is heated and then forged into a square ingot; wherein the diameter of the alloy ingot is Φ120mm; the heating temperature is 880℃, the holding time is 100min, and the side length of the cross section of the forged square ingot is 40mm.

[0085] S2, Hot rolling: The square ingot is hot rolled through a multi-pass square-round-square profile until the bar diameter is Φ6mm; the hot rolling parameters are: heating temperature is 880℃, and holding time is 50min;

[0086] S3, Hot drawing: The bar is hot drawn in multiple passes until the diameter of the bar is Φ2mm; the hot drawing parameters are: heating temperature is 850℃, and holding time is 48min;

[0087] S4, intermediate cold drawing: The bar is subjected to multiple cold drawing passes, wherein the deformation amount of a single pass of intermediate cold drawing is 15% to 20%, and the cumulative deformation amount of intermediate cold drawing is 35% to 50%.

[0088] S5, Intermediate Annealing Treatment: The cold-drawn bar is subjected to intermediate annealing treatment. The intermediate annealing treatment process is as follows: heating temperature 750℃, holding time 3min, and cooling method is air cooling.

[0089] S6. Repeat steps S4 to S5 until the diameter of the bar reaches Φ0.5mm;

[0090] S7, Final Cold Drawing: The bar is cold drawn in multiple passes until the wire size reaches Φ0.32mm. The deformation per pass of the final cold drawing is 10% to 20%; the cumulative deformation of the final cold drawing is 59%.

[0091] S8, Finished product annealing treatment: The finished product annealing treatment is carried out on the final cold-drawn wire. The finished product annealing treatment process is as follows: heating temperature 450℃, holding time: 60min, cooling method is air cooling. The finished product annealing treatment yields the nickel-titanium alloy wire with a diameter of Φ0.32mm.

[0092] Experimental Example 1

[0093] Stress-strain tests were performed on the nickel-titanium alloy wire prepared in Example 1:

[0094] Testing process:

[0095] A 100mm gauge length alloy wire was cut and its ends were clamped together using a capillary tube to prepare a tensile specimen. The stress-strain test was performed using a SHIMAZU-100KN tensile tester at a tensile speed of 2mm / min. An extensometer was not used during the test; the corresponding strain was calculated from the displacement and gauge length.

[0096] Test results:

[0097] The stress-strain curves obtained from the test are as follows: Figure 3 As shown, the measured untwisting stress was 157 MPa, and the recovery strain rate was 4.5%.

[0098] Experimental Example 2

[0099] DSC curve tests were performed on the nickel-titanium alloy wires prepared in Examples 1, 2, and 3:

[0100] Testing process:

[0101] Approximately 20 mg of alloy wire was cut and its heating and cooling curves were tested using a TA differential scanning calorimeter at a rate of 5 °C / min.

[0102] Test results:

[0103] The DSC curve of Example 1 obtained by testing is as follows: Figure 4 As shown, the measured critical phase transition temperature is A. s =56.96℃, A f =75.89℃, R s =59.18℃ and M s =16.6℃; the critical phase transition temperature of Example 2 is A s =55.86℃, A f =77.08℃, R s =59.28℃ and M s =17.54℃; the critical phase transition temperature of Example 3 is A s =56.96℃, A f =58.74℃, R s =57.61℃ and M s =11.50℃.

[0104] Experimental Example 3

[0105] Functional fatigue resistance tests were conducted on nickel-titanium alloy wires prepared according to Examples 1, 2, and 3, and commercially available shape memory nickel-titanium alloy wires.

[0106] Testing process:

[0107] A 150mm nickel-titanium alloy wire was cut, and fatigue cycle specimens were prepared by clamping both ends of the wire with capillary tubes. The specimen was then placed horizontally on a test platform, with one end secured to the platform's base and the other end connected to a suspended load via a hook, wire, and pulley. Connecting the capillary tubes to the circuit applied a current to the nickel-titanium alloy wire caused it to contract, pulling up the suspended load. Without current applied, the wire elongated because the tensile stress exceeded the wire's untwisting stress. Based on the parameters measured in Example 1, a load stress level of 175MPa was selected. For a Φ0.38mm nickel-titanium alloy wire, a load of 2.024kg was required. The power supply parameters were selected as 24V and 3A, sufficient to heat the wire to a temperature of A. f Above this point, a relay is connected in series in the circuit to allow the current to be applied cyclically. The energizing time is set to 3A and the de-energizing time to 30s, so that the nickel-titanium alloy wire can be fully cooled.

[0108] Test results:

[0109] The fatigue curve of 100 tensile-thermal cycles obtained by testing the nickel-titanium alloy wire prepared in Example 1 is shown below. Figure 5 As shown.

[0110] The fatigue curve of a commercially available shape memory nickel-titanium alloy wire of the same size and tested using the same method after 100 tensile-thermal cycles is shown below. Figure 6 As shown.

[0111] Functional fatigue testing revealed that the commercially available alloy wire accumulated 0.1% plastic strain per cycle, while the nickel-titanium alloy wire prepared in Example 1 accumulated only 0.0085% plastic strain per cycle. Although the two have similar recovery strains, the commercially available alloy wire cannot adequately meet the requirements of repeated use, high fatigue resistance, and low plastic strain accumulation in aerospace unlocking devices. In contrast, the alloy wire prepared according to Example 1 of this invention has a plastic strain accumulation performance that is an order of magnitude lower than that of the commercially available alloy wire per cycle, making it more suitable for the application requirements of shape memory alloy unlocking devices.

[0112] Using the same side-view method, the fatigue curves obtained by testing the nickel-titanium alloy wires prepared in Examples 2 and 3 after 100 tensile-thermal cycles showed that the nickel-titanium alloy wire prepared in Example 2 had a plastic strain accumulation of 0.0094% per cycle, and the nickel-titanium alloy wire prepared in Example 3 had a plastic strain accumulation of 0.0256% per cycle.

[0113] Therefore, when designing an unlocking device, using the alloy wire prepared by this invention can greatly reduce design redundancy, or ensure the unlocking device operates stably for an ultra-long lifespan under the same design redundancy.

[0114] Test Example 4

[0115] Microstructure analysis of alloy wire:

[0116] Testing process:

[0117] A slice is taken radially from the alloy wire using a focused ion beam. The sampling location of the alloy wire is as follows: Figure 7 As shown. Its microstructure was characterized using transmission electron microscopy (TEM) on a JEOL JEM-2100Plus instrument with an accelerating voltage of 200 kV.

[0118] Test results:

[0119] The microstructure of alloy wire, such as Figure 8 As shown.

[0120] Combination Figure 8The plastic processing and heat treatment process of the nickel-titanium alloy wire described in this invention yields the following: During the preparation process, a large deformation of over 50% followed by final cold drawing fully breaks down the grains within the alloy wire. After annealing to regulate the microstructure, an equiaxed crystal structure with a grain size of approximately 50–100 nm is formed, exhibiting typical lath-like characteristics of martensitic phase transformation within the grains. When the alloy wire is stretched to a specific shape, it is essentially a process of detwinning the non-twinned martensite within the microstructure. The detwinning process ends when the strain reaches the maximum recoverable strain. When the alloy wire is shrunk by electrical heating, i.e., when the shape memory effect occurs, it mainly involves a reverse martensitic phase transformation that restores the crystal structure to austenite, thereby recovering the deformation.

[0121] Studies have shown that the accumulation of plasticity is mainly due to the activation of various lattice defect mechanisms under the combined effects of stress and temperature during electrical heating. This leads to lattice mismatches in the alloy wire's microstructure, resulting in irreversible plastic deformation such as dislocations, specific twins, and twisting. When the grain size is large, plasticity accumulation is more likely to occur in regions with severe lattice mismatches, such as large-angle grain boundaries, during the reverse martensitic phase transformation. However, by controlling the microstructure through a reasonable multi-pass cold drawing-heat treatment method, extremely fine nanocrystalline structures were produced. When such a microstructure exhibits shape memory effects, the abundance of adjacent grains and orientations allows for well-coordinated phase transformations between grains, reducing the likelihood of lattice mismatches at grain boundaries and effectively suppressing dislocation activity at these boundaries. The A-type microstructure of this microstructure... f The point is significantly lower than the A of the coarse-grained structure. f The results show that only a small degree of supercooling (phase transformation driving force) is required for the martensitic / reverse martensitic phase transformation to occur, further illustrating the important role of grain boundaries and orientation fit in optimizing the shape memory effect. The cold working-heat treatment method in this case study utilizes this principle, significantly improving the shape memory effect of shape memory alloy wires by refining the grains and substantially introducing grain boundaries.

[0122] The embodiments of this application have been described above with reference to the accompanying drawings. Unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other. This application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of this application.

Claims

1. A process for plastic forming and heat treatment of nickel-titanium alloy wire for aerospace unlocking device drive, characterized in that, The elemental composition of the nickel-titanium alloy wire, by weight percentage, includes: 49.9-50.1% Ni, with the balance being Ti and other unavoidable impurity elements; wherein, the impurity content, by weight percentage, is: C < 0.01%, O < 0.05%, N < 0.001%, H < 0.0002%. The plastic forming and heat treatment process of the nickel-titanium alloy wire includes the following steps: S1, forging: heating the alloy ingot and then forging it into a square ingot; S2, Hot rolling: Square ingots are hot rolled through a multi-pass square-round-square profile until the bar diameter is ≤ Φ8mm; S3, Hot drawing: The bar is hot drawn in multiple passes until the bar diameter is ≤ Φ3mm; S4, Intermediate Cold Drawing: The bar is subjected to multiple cold drawing passes, wherein the deformation per pass of the intermediate cold drawing is 5% to 20%; the cumulative deformation of the intermediate cold drawing is 29% to 60%. S5, Intermediate Annealing Treatment: The intermediate annealing treatment is carried out on the bar after intermediate cold drawing. The intermediate annealing treatment process is as follows: heating temperature 680~750℃, holding time 1~3min, and cooling method is air cooling or wind cooling. S6. Repeat steps S4 to S5 until the diameter of the bar reaches Φ0.5 to 2 mm. S7, Final Cold Drawing: The bar is cold-drawn in multiple passes until the dimensions of the cold-drawn wire meet the requirements of the finished product. The deformation amount per pass in the final cold drawing is 5% to 20%. S8, Finished product annealing treatment: After the final cold-drawn wire is subjected to finished product annealing treatment, the nickel-titanium alloy wire is obtained.

2. The nickel-titanium alloy wire plastic forming-heat treatment process according to claim 1, characterized in that, The diameter of the nickel-titanium alloy wire is Φ0.32~0.42mm.

3. The nickel-titanium alloy wire plastic forming-heat treatment process according to claim 1, characterized in that, In step S1, the diameter of the alloy ingot is Φ80~120mm; the heating temperature is 850-880℃; the holding time is 80~100min; and the side length of the cross section of the forged ingot is 60~40mm.

4. The nickel-titanium alloy wire plastic forming-heat treatment process according to claim 1, characterized in that, In step S2, the hot rolling parameters are: heating temperature of 850-880℃, holding time of 30-50min, and hot rolling through a multi-pass square-round-square die to a bar diameter of Φ6-8mm.

5. The nickel-titanium alloy wire plastic forming-heat treatment process according to claim 1, characterized in that, In step S3, the hot drawing parameters are: heating temperature of 700-850℃, holding time of 35-48min, and after multiple hot drawing passes, the diameter of the bar is Φ1-3mm.

6. The nickel-titanium alloy wire plastic forming-heat treatment process according to claim 1, characterized in that, In step S7, the cumulative deformation of the final cold drawing is ≥40%.

7. The nickel-titanium alloy wire plastic forming-heat treatment process according to claim 1, characterized in that, In step S8, the annealing process for the finished product is as follows: heating temperature 400~450℃, holding time 30~60min, and cooling method is air cooling.

8. A nickel-titanium alloy wire for driving an aerospace unlocking device, characterized in that, The nickel-titanium alloy wire is prepared by the nickel-titanium alloy wire plastic processing-heat treatment process described in any one of claims 1 to 7.

9. A spacecraft unlocking device, characterized in that, The aerospace unlocker comprises a nickel-titanium alloy wire prepared by the plastic processing-heat treatment process of nickel-titanium alloy wire as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing high-purity NiTi alloy wire

    CN111593231A

  • Preparation method of hyperelastic nickel-titanium alloy wire and hyperelastic nickel-titanium alloy wire

    CN117364003A